2019
DOI: 10.1002/celc.201801638
|View full text |Cite
|
Sign up to set email alerts
|

Extended Limits of Reversible Electrochemical Lithiation of Crystalline V2O5

Abstract: Although lithium intercalation into vanadium (V) oxide was studied over decades, exact compositional stability limits for γ-Li x V 2 O 5 phase, which can be reversibly lithiated and delithiated, are still not clear. Using operando and ex-situ synchrotron X-ray diffraction, we traced phase composition of the V 2 O 5 electrodes containing reduced graphene oxide during its lithiation and delithiation. We found that coating of micron-sized V 2 O 5 particles by reduced graphene oxide yields the material providing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…[ 40 ] The anode initially has an γ ‐phase consisting of intensively puckered layers with characteristics of [VO 5 ] “up and down” oriented pyramids due to the deep lithiation. [ 43 ] Upon discharging of a full battery, Li‐ion de‐intercalation takes place in the anode, yielding the γ ‐ to δ ‐phase transformation of Li x V 2 O 5 . The cathode and anode would share the same formula ( δ ‐Li 1 V 2 O 5 ) in theory at the end of discharging.…”
Section: Resultsmentioning
confidence: 99%
“…[ 40 ] The anode initially has an γ ‐phase consisting of intensively puckered layers with characteristics of [VO 5 ] “up and down” oriented pyramids due to the deep lithiation. [ 43 ] Upon discharging of a full battery, Li‐ion de‐intercalation takes place in the anode, yielding the γ ‐ to δ ‐phase transformation of Li x V 2 O 5 . The cathode and anode would share the same formula ( δ ‐Li 1 V 2 O 5 ) in theory at the end of discharging.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the phase transitions of α ⇌ ε, ε ⇌ δ, and δ ⇌ γ-Li x V 2 O 5 appear in the range of 0.01 < x < 0.35, 0.35 < x < 0.70, and 0.70 < x < 1.25, respectively (Note S2, Supporting Information). [18,29,37,38] Furthermore, adjusting the working potential windows can tune the number of Li To get further insight into the structural evolution of VON, ex situ XRD of VON electrode with several typical GCD states at 4.00-2.00 V (vs Li/Li + ) was studied. VON electrode shows welldefined reflections of the orthorhombic V 2 O 5 phase at initial state ( Figure 3c).…”
Section: Doi: 101002/smll202003816mentioning
confidence: 99%
“…It is found that the phase transitions of α ⇌ ε, ε ⇌ δ , and δ ⇌ γ‐Li x V 2 O 5 appear in the range of 0.01 < x < 0.35, 0.35 < x < 0.70, and 0.70 < x < 1.25, respectively (Note S2, Supporting Information). [ 18,29,37,38 ] Furthermore, adjusting the working potential windows can tune the number of Li + ( x ) in Li x V 2 O 5 , resulting in its successive phase transformations. The C sp nearly reaches the theoretical capacity ( C t ) of V 2 O 5 , exhibits 145 mAh g −1 (Li 0.99 V 2 O 5 , one Li ion insertion regime) and 291 mAh g −1 (Li 1.98 V 2 O 5 , two Li ion insertion regime) at 2.60 and 2.00 V in Li + intercalation (discharging) process, while the reverse order at 2.90 and 4.00 V in Li + de‐intercalation (charging) process, respectively.…”
Section: Figurementioning
confidence: 99%